Greater sage‐grouse sex ratios in Utah: Implications for reporting population trends. Issue 8 (15th October 2013) - Guttery, Michael R.; Messmer, Terry A.; Thacker, Eric T.; Gruber, Natasha; Culumber, C. Mae
ABSTRACT: Greater sage‐grouse ( Centrocercus urophasianus ; sage‐grouse) are a species of conservation concern throughout western North America. Obtaining valid population estimates is essential to understanding population trajectories and the effects of management. Counts of male sage‐grouse attending leks during the breeding season are used directly as a population index or to estimate the breeding population size by assuming a detection probability and sex ratio. In the latter case, managers often assume a 2:1 female‐biased ratio. However, this sex ratio has not been validated and may result in biased population estimates. We evaluated sex ratios at hatch, 42 days of age, and at harvest to determine if sex ratios were biased for sage‐grouse in Utah. Sex ratios at hatch and at 42 days of age did not differ from parity. Harvest data suggested that sage‐grouse may exhibit a slight female‐biased sex ratio (1.458:1) in the fall. Wildlife management agencies should use caution when using lek count data to estimate population size if sex ratios have not been validated. © 2013 The Wildlife Society.